ASSESSMENT OF SELF-EXTRACTED CELLULOSE FROM ORYZA SATIVA FOR DESIGN OF CONTROLLED DRUG DELIVERY SYSTEM OF DALFAMPRIDINE - JYOTHI B, JEEVANA; M, MOUNIKA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The main objective of the present work includes extraction of cellulose from Oryza sativa (OS), characterization of cellulose, development of controlled release tablet dalfampridine using cellulose of OS, and in vitro evaluation. Methods: Dry powdered OS husk sample was extracted with a mixture of hexane and methanol (2:1, v/v) using soxhlation method and was characterized by solubility, melting point determination, differential scanning calorimetry (DSC), and Fourier-transform infrared (FTIR) analysis. Compatibility between dalfampridine and the mixture of cellulose with dalfampridine was confirmed by FTIR and DSC analysis. Then, controlled drug delivery system of dalfampridine were prepared as directly compressed tablets using various compositions containing OS cellulose, hydroxypropyl methylcellulose (HPMC), dicalcium phosphate, and magnesium stearate (8 nos. F1 to f8) and were evaluated. Results: Cellulose was extracted from OS extract to possess its ideal characteristics. Dalfampridine and its mixture with cellulose were compatible according to FTIR and DSC analysis. Directly compressed tablets made with 10 mg of dalfampridine and OS cellulose, HPMC, dicalcium phosphate, and magnesium stearate evidenced prolonged and controlled drug delivery of dalfampridine for 12 h. Formulation made with OS cellulose 250 mg, HPMC 20 mg, dicalcium phosphate 40 mg, and magnesium stearate 5 mg was ideal without burst release. Conclusion: Cellulose extracted from OS is used successfully for the production of directly compressed tablets of dalfampridine to elicit optimum characteristics including controlled drug delivery for 12 h.